Post-processing effects on microstructure, interlaminar and thermal properties of 3D printed continuous carbon fibre composites. (1st April 2021) - Pascual-González, C.; San Martín, P.; Lizarralde, I.; Fernández, A.; León, A.; Lopes, C.S.; Fernández-Blázquez, J.P.
Abstract: 3D printing of continuous carbon fibre reinforced composites (CCFRC) based on fused filament fabrication (FFF) has a great potential for reproducing robust and complex geometries, generating little waste. However, 3D printed CCFRC present relatively poor interlaminar bonding and high void content in comparison to traditional composites. This work analyses the post-processing temperature effects on microstructure, interlaminar properties and thermal stability of the printed CCFRC. Treated pieces at 150 °C showed a reduction of porosity by approximately 87% and improved interlaminar strength by 145%, without modifying nominal dimensions. In addition, the increase in T g (from 109 °C to 131 °C) is ascribed to a drying effect during the post-processing, which reduces the plasticisation of the treated parts and contributes to the general enhancement of mechanical properties of printed CCFRC coupons. The proposed post-processing moves this technology towards the development of functional composite components for high-performance structural applications.